Vertaalteoretiese benaderings by Kinderbybelvertaling - Brink, Theodora Petronella (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Afrikaans and Dutch))--University of Stellenbosch, 2010.